Jewish literatures and cultures in Southeastern Europe - Hansen-Kokoruš, Renate,Terpitz, Olaf (Böhlau Verlag, 2021)
The volume offers an overview of the diverse Jewish experiences in Southeastern Europe from the 19th to the 21st centuries, and the various forms and strategies of their representation in literature, the arts, historiography and philosophy.Southeastern Europe is characterized by a high degree of ethnical, religious and cultural diversity. Jews, whether Sephardim, Ashkenazim or Romaniots – settling there in different periods – experienced divergent life worlds which engendered rich cultural production. Though recent scholarly and popular interest in this heterogeneous region has grown impressively, Jewish cultural production is still an under-researched area.The volume offers an overview of the diverse Jewish experiences in Southeastern Europe from the 19th to the 21st centuries, and the various forms and strategies of their representation in literature, the arts, historiography and philosophy, thus creating a dialogue between Jewish studies, Balkan studies, and current literary and cultural theories. Angaben zur beteiligten Person Terpitz: PD Dr. Olaf Terpitz ist Slawist, Literatur- und Kulturwissenschaftler an der Universität Wien. Er befasst sich komparatistisch mit slawisch-jüdischen Begegnungen, Transfer- und Übersetzungsprozessen. Angaben zur beteiligten Person Lamprecht: Univ.-Prof. Dr. Gerald Lamprecht leitet das Centrum für Jüdische Studien der Universität Graz. Seine Forschungsschwerpunkte liegen auf der jüdischen Regionalgeschichte, der Geschichte des Antisemitismus und der Verfolgung der jüdischen Bevölkerung der Steiermark während der Zeit des Nationalsozialismus
10.7767/9783205212904
Keywords: Konferenzschrift; Judentum in Südosteuropa; Ashkenazim; Balkan Studies; Roma; Sephardim; Jewish Studies